EOCENE NAUTILOIDS FROM THE BAJA CALIFORNIA PENINSULA, MEXICO: RECORDS, DESCRIPTION OF A NEW SPECIES, AND BIOGEOGRAPHIC IMPLICATIONS - Priscila Morales-Ortega; Gerardo Gon´zalez-Barba; Mariana Díaz-Santana-Iturrios; Tobias Schwennicke (Publicación Electrónica de la Asociación Paleontológica Argentina, 2023)
Several cephalopods from the Eocene have been recorded along the Pacific coast of North America. Each new record incorporates relevant knowledge to infer the paleobiology of this group. In this study, we report two nautiloids (subclass Nautiloidea) from the Ypresian found in the Tepetate Formation. One specimen was identified as Eutrephoceras hannai, and the other was designated as species nova, Nautilus sudcalifornianus. We found that the suture shape, especially in the lateral lobe, is the most conspicuous diagnostic feature to discriminate nautiloids. Moreover, the biological material evaluated in our study constitutes the southernmost geographic distribution of the two species and the most ancient record of Nautilidae for the Eocene. Due to the characteristics detected in the specimens analyzed here and previous studies that describe the faunal diversity of the formation, we hypothesize that this area was an idoneous site for spawning and growth of young stages of E. hannai and N. sudcalifornianus sp. nov. during the Eocene. Thus, our study supports the hypothesis that extant nautiloids migrate towards warm shallow water areas for spawning and growth of the juvenile stage and suggests that this migratory behavior is ancient within the subclass. With this research, we provide new insights into the taxonomy, biology, ecology, and biogeography of nautiloids from the Eocene. Additionally, the Tepetate Formation has great geological and paleontological relevance given the faunal diversity discovered in this area increases the malacological record for the northeastern Pacific.